2003
DOI: 10.1002/pola.10777
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties and fracture toughness of epoxy resins cured by phosphonium and pyrazinium salts as latent cationic initiators

Abstract: In this work, the latent thermal cationic initiators triphenyl benzyl phosphonium hexafluoroantimonate (TBPH) and benzyl-2-methylpyrazinium hexafluoroantimonate (BMPH) were newly synthesized and characterized with IR, 1 H NMR, and P NMR spectroscopy. The thermal and mechanical properties of difunctional epoxy [diglycidyl ether of bisphenol A (DGEBA)] resins cured by 1 phr of either TBPH or BMPH were investigated. The DGEBA/TBPH system showed a higher curing temperature and a higher critical stress intensity fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Instead, they promote transfers and decrease the overall rate of the polymerization. It is worth noting that alcohols and water could also accelerate the curing rate as the role they play is very dependent on the structure of both the monomers [107,108] and the initiator [109]. This will be further discussed in Section 4.2.…”
Section: Page 12 Of 163mentioning
confidence: 97%
“…Instead, they promote transfers and decrease the overall rate of the polymerization. It is worth noting that alcohols and water could also accelerate the curing rate as the role they play is very dependent on the structure of both the monomers [107,108] and the initiator [109]. This will be further discussed in Section 4.2.…”
Section: Page 12 Of 163mentioning
confidence: 97%
“…For use on a large variety of polar solids, it is needed to have at least two-unidentical liquids to calculate the polar surface energy, if the values of γ L L and W SP L are known, such as water, diiodomethane, ethylene glycol and glycerol (Park, 1999;Wu, 1982;Park et al, 2003). However, recent studies (Fabretto et al, 2004;Landry et al, 1996;Elmoursi and Patel, 2004) have shown that using two liquids according to geometric mean gives a significant variety of unsatisfactorily energetic results when the testing liquids were varied in a composition of two liquids such as water-diiodomethane, water-ethylene glycol, diiodomethane-ethylene glycol and, etc.…”
Section: Surface Properties and Adhesion Strengthsmentioning
confidence: 99%
“…Therefore, in this study, the Coats-Redfern equation derived from the integral method is used to determine the decomposition activation energy (E d ) as follows: 15,16 (…”
Section: Conversionmentioning
confidence: 99%